Proyecto de factibilidad para la creación de una empresa textil productora y comercializadora de Indumentarias típicas de la nacionalidad Siekopaai, en el cantón Shushufindi, de la provincia de Sucumbíos, para el año 2016 - Piaguaje Shiguango, Mayra Fanny (2017)
The general objective of this thesis was to determine the feasibility to promote the textile industry, through technical procedures in the production of typical clothing, considering that it is important to preserve the tradition on the use of clothing to strengthen the cultural identity of nationality Siekopaai, who lives in the Shushufindi canton, province of Sucumbíos. The problem that was located was the low production of the typical clothing, because the siekopaai woman no longer makes more frequently, making use of this activity only for special occasions such as ceremonies and cultural festivals. For the development of the theoretical part, the techniques of bibliographic collection were applied, which consisted of preparing the theory according to the research topic. In the determination of the result, empirical data collection techniques such as direct observation, surveys of families from the Shushufindi canton were used to determine demand and supply, tabulation and interpretation of the results were performed using the statistical method. The use of all these methods allowed us to reach the culmination of the present work since to achieve this we had to follow the steps of application understanding and demonstration thereof. With regard to the techniques, a survey was carried out on 374 families from the Shushufindi canton and a survey of 11 local clothing producers. After conducting the research the following results and conclusions were obtained: In the market study, the surveys were tabulated and analyzed, determining the potential demand of 10,700, the actual demand 10,272, the actual demand for 37,389 typical clothing, the supply of 2,772 apparel and the unsatisfied demand for 34.665 clothing. The installed capacity of the project determines that the company will be able to produce 8,320 typical clothing and its used capacity will be 6,240 clothing, which represents 75% of the capacity used for the first year, in addition determines the location of the same that will be Located in the canton Shushufindi, in the streets via Providencia and via San Pablo. Next, the engineering of the project is developed, determining the production process, which demands the use of suitable machines and equipment, which will guarantee a quality product at moderate prices, process diagrams, operational and management characteristics, technical requirements Such as equipment, facilities, furniture and appliances. Likewise, a legal and administrative study was carried out, determined as a Limited Liability Company, and with the functional organizational structure at the hierarchical levels, both Legislative, Executive, Adviser, Support and Operational Level, as well as function manuals, organizational charts ; Which serve as guidelines for implementing a good organization. The project achieves an investment of 84,807.82, the financial evaluation presents the following results: According to the NPV of the present project gives us a positive value of 35,939.59 dollars, indicating that the project or investment is convenient. For the present project, the IRR is 24.87%, this being a satisfactory value to carry out the project, the time required to recover the original investment would be 3 years and 8 months and one day, for the present project, the sensitivity values are less than One, therefore the changes in costs and revenues increased 22.33 and 14.90%, respectively, do not affect the project. Subsequently, the most significant conclusions and recommendations of the project.